Clinical Profile and Therapeutic Response of Scrub Typhus in Children: A Recent Trend from Eastern India. (23rd May 2018) - Basu, Suprit; Saha, Arpan; Sarkar, Sumantra; Sinha, Malay Kumar; Das, Mrinal Kanti; Datta, Ranjabati; Hazra, Avijit; Datta Kanjilal, Sumana; Datta, Supratim
Abstract: Objective: The aim of this study was to assess the clinico-laboratory parameters, complications and therapeutic responses in children with scrub typhus in Eastern India. Materials and methods: In this prospective, observational study, all children (age, <12 years) with suspected scrub typhus with a compatible clinical scenario were enrolled consecutively over six months. Cases confirmed by means of a positive IgM serology or a positive Weil–Felix reaction (OXK = 1/80 or above) were administered enteral doxycycline (4.5 mg/kg/day). Results: Out of 94 recruited children, 61 had confirmed scrub typhus (mean age = 6.1 years, M:F = 1.1:1) with or without complications and having a considerably higher incidence of neurological presentation (meningoencephalistis n  = 21, 34.4%). The most frequent manifestations included vomiting ( n  = 39, 63.9%), abdominal pain ( n  = 33, 54.1%), lymphadenopathy ( n  = 36, 59%), hepatosplenomegaly ( n  = 32, 52.5%), pedal edema ( n  = 32, 52.5%) and eschar formation ( n  = 30, 49.2%). Low hemoglobin levels, leukocytosis, thrombocytopenia, hypoalbuminemia, hyponatremia, increased liver enzymes and increased C-reactive protein were associated with delayed defervescence (>48 h) Conclusion: Scrub meningoencephalitis, with a notably higher incidence, showed favorable therapeutic response. Prompt and empiric doxycycline therapy could be lifesaving.